Pathomorphology of cats with myocardial infectious peritonitis - G. I. Kotsyumbas; M. R. Khalaniia (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки, 2019)
The article presents the results of macroscopic and microscopic examinations of myocardial cats in wet and mixed forms of FIP. A pathoanatomical study of 19 cat carcasses, aged from 3 months to 7 years, was diagnosed with infectious peritonitis during life (on the basis of anamnesis, clinical features, morphological and biochemical blood test, ultrasound, Rivalt test and FCVetx rapid test VetE.) All animals were kept at home. For the microstructural study, samples of cats' hearts were selected, which were fixed in 10% aqueous formalin neutral solution, Carnua, Buen solutions and 96 ° ethyl alcohol. Histogram sections were stained with hematoxylin and eosin staining, picrofuxin (Van Gizon), PAS reaction (McManus), methyl green pyronin (Brache), Malory, and examined under a microscope. Histological examination of the cardiac muscle of cats in various forms of infectious peritonitis revealed changes of non-inflammatory and inflammatory nature. In the exudative form, non-inflammatory processes prevailed. In the myocardium, the most severe changes occurred in the capillaries, the walls of the arterial vessels and the stroma, which were characterized by diapedic hemorrhage, mucoid and fibrinoid swelling and necrosis of the walls of the arterioles. Disorganization of connective tissue was accompanied by stratification of connective tissue fibers and impregnation of weakly oxyphilic, PAS-positive compounds of the intermuscular lumen, which was combined with dystrophic changes in cardiomyocytes. In the mixed form, proliferative-destructive vasculitis, diffuse or focal lymphoid-histiocytic infiltrates in the myocardium prevail. The revealed optical changes in the structural elements of the heart indicated a sharp weakening of the contractile function of cardiomyocytes and heart failure. In addition, it should be noted that the characteristic morphological manifestation for immunocomplex diseases is the development of vasculitis, which is preceded by fibrinoid necrosis of the walls of the arterial vessels and intensive infiltration of their circulatory elements, and these changes occurred in infectious peritonitis of cats.